Liver mitochondrial function in ZDF rats during the early stages of diabetes disease. Issue 3 (4th February 2016) - Vial, Guillaume; Le Guen, Marie; Lamarche, Frédéric; Detaille, Dominique; Cottet‐Rousselle, Cécile; Demaison, Luc; Hininger‐Favier, Isabelle; Theurey, Pierre; Crouzier, David; Debouzy, Jean‐Claude; Dubouchaud, Hervé; Fontaine, Éric
Abstract: The aim of this study was to characterize the early alterations of the liver mitochondrial function in ZDF (fa/fa) rats that develop diabetes compared to that of their lean counterparts ZDF (fa/+). Liver mitochondrial function was examined in 11‐ and 14‐week‐old ZDF (fa/fa) and ZDF lean (fa/+) rats. Oxygen consumption, H2 O2 release, calcium retention capacity (CRC), membrane potential, membrane fluidity, and fatty acid composition were analyzed. State 3 oxygen consumption with palmitoyl‐carnitine increases between 11 and 14 weeks of age in lean but not in diabetic animals. This response was not seen with other substrates, suggesting that the use of fatty acids is impaired in diabetic rats. H2 O2 release was lower in 14‐week‐old ZDF (fa/fa) rats as compared to ZDF lean (fa/+). These changes were not associated with differences in enzymatic activities of the respiratory complexes, suggesting regulatory mechanisms independent of their expression levels. Membrane fluidity and composition analyses show only slight effects linked to diabetes progression. The most salient feature was a reduction in CRC in the presence of CsA, an effect reflecting PTP dysregulation. Our data suggest few changes of mitochondrial function in ZDF fa/fa rats. At the age of 11 weeks, liver mitochondria have mainly a reduced effect of CsA on CRC. Abstract : ZDF liver mitochondrial function: Our data suggest few changes of mitochondrial function in ZDF fa/fa rats. At the age of 11 weeks, liver mitochondria have mainly a reduced effect of CsA on CRC.